2013
DOI: 10.1182/blood-2012-10-461749
|View full text |Cite
|
Sign up to set email alerts
|

The level of residual disease based on mutant NPM1 is an independent prognostic factor for relapse and survival in AML

Abstract: Key Points• NPM1 RT-PCR levels .1%are associated with poor overall and disease-free survival in AML patients treated with chemotherapy.• NPM1 MRD levels .10% are associated with poor overall and disease-free survival in AML patients after allogeneic transplantation.Mutations of the NPM1 gene (NPM1 mut ) are among the most common genetic alterations in acute myeloid leukemia and are suitable for minimal residual disease detection. We retrospectively investigated the prognostic impact of NPM1 mut -based minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
170
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 36 publications
14
170
0
Order By: Relevance
“…Krönke et al, 10 and Shayegi et al 11 analyzed clinically relevant MRD checkpoints in NPM1-mutated patients. They, too, identified MRD assessment after induction therapy, or after the achievement of complete remission, as one of the most important MRD checkpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krönke et al, 10 and Shayegi et al 11 analyzed clinically relevant MRD checkpoints in NPM1-mutated patients. They, too, identified MRD assessment after induction therapy, or after the achievement of complete remission, as one of the most important MRD checkpoints.…”
Section: Discussionmentioning
confidence: 99%
“…1,15 NPM1 mutations are reliable markers for monitoring MRD after conventional chemotherapy, allogeneic HSCT, or during the subsequent follow-up. 10,11,16,17 There has been some discussion on the stability of this MRD marker in relapse, but NPM1 mutations could be detected in at least 91% of all relapsed patients. 10,18 In this study, we analyzed MRD monitoring by RT-PCR in 158 adult patients with NPM1 A, B and D mutations treated with high-dose cytarabine induction therapies within the AMLCG 1999, 2004 and 2008 trials.…”
Section: Correspondence: Maxhubmann@meduni-muenchendementioning
confidence: 99%
“…Of interest, these cutoff values are significantly lower than those identified in other studies performed in the transplant setting. [7][8][9] Comparing WT1 with NPM1 mut in the relapse cohort, nine out of the eleven patients (82%) had WT1 overexpression (defined according to the threshold identified by Cilloni et al 11 ) during their follow-up, but most of them (seven out of nine) had just a single over-threshold value before relapse, with approximately 1 month of advance before the clinical event. Besides, in the longterm CR cohort, 11 out of 17 patients showed WT1 overexpression in at least one BM evaluation, suggesting limited leukemia specificity (35%).…”
mentioning
confidence: 99%
“…4,5 In line with that, numerous studies have demonstrated the usefulness of landmark analyses and longitudinal monitoring of NPM1 mut in AML patients after chemotherapy. 6,7 However, information on the clinical utility of NPM1 mut quantitative monitoring in the post-transplantation setting are to date more limited, [7][8][9] and thus represent the specific focus of our present study.…”
mentioning
confidence: 99%
See 1 more Smart Citation